A Research On Surgical Nurses’ Critical Thinking Dispositions and Attitudes Towards Evidence-Based Nursing - Taşçı, Ömer; Özer, Nadiye (Dokuz Eylul University, 2023)
Background: Perioperative care settings are places where, at times, complex, fast-paced, and unpredictable situations can occur. In this care setting, critical thinking and evidence-based nursing aiming at rational decision making and the use of the best research evidence are essential. Objectives: The research was conducted to examine nurses’ critical thinking dispositions and attitudes towards evidence-based nursing. Methods: The descriptive study was carried out between December 2017–December 2018. It was conducted with 317 nurses working at a state unıversity Health Research and Application Centre and a state hospital. In order to collect data, descriptive characteristics form, profession perception form, California Critical Thinking Disposition Invertory (CCTDI) and Evidence Based Nursing Attitude Questionnaire (EBNAQ) were used. The data were analyzed by percentage, mean, independent samples t, one way ANOVA, Mann Whitney-U, Kruskall Wallis, Cronbach’s ? and Pearson correlation tests. Results: The total score was calculated as 255.57 ± 27.46 (middle level) in CCTDI and as 59.17 ± 8.43 (positive) in EBNAQ. A positive significant relation was determined (p <.05) between all sub-dimensions and total mean scores except for the sub-dimension “Self Confidence” of CCTDI and the sub-dimensions “Evidence-Based Practice Invention” and “Emotions Related to Evidence-Based Nursing” of EBNAQ. Conclusion: As a result, in nurses, the increase in work intensity increased the tendency of critical thinking; using evidence-based practices frequently, wanting to learn more about evidence-based practices, receiving training on evidence-based practice and following scientific studies positively affect the attitude towards evidence-based nursing; As critical thinking tendency increases, it can be said that the attitude towards evidence-based nursing is positively affected. © 2023, Dokuz Eylul University. All rights reserved.
Cerrahi Hemşirelerin Eleştirel Düşünme Eğilimleri ile Kanıta Dayalı Hemşireliğe Yönelik Tutumlarının İncelenmesi
Keywords: Critical Thinking; Evidence-Based Nursing; Nurses; Surgical